Analisis Faktor-faktor yang mempengaruhi Job Performance pada industri otomotifi motor di batam - Kingsman, Eric; Fatyandri, Adi Neka (Universitas Pelita Harapan Medan, 2018)
Automotive involvement has become important in daily life basis whether it is for reaching a location or speeding up trips. In this era automotive sector is growing and has a huge unit sales from a few company such as Honda, Suzuki, Kawasaki and Yamaha. This study is to analyze the effect of job performance on the automotive industry in Batam. There are 3 factors that influence job performance. The 3 factors are Social Support, Self-Efficacy and Organizational Structure. The targeted population are employees of motorcycle automotive in Batam, Indonesia. Whereas the sample that will be studied on will be the employees from motorcycle automotive which is still working. 110 questionnaire have been distributed to various location in Batam but there were 4 questionnaire which invalid and 6 not fully answered. Therefore, there is only 100 questionnaire left that can be used for the research. The result of this study have shown that 2 out of 3 factors have an influence on job performance for employees working at automotive sector in Batam. These factors are Self-Efficacy and Organizational Structure. While Social Support has no influence on job performance for employees working at automotive sectors. Keywords: Job Performance, Social Support, Self-Efficacy and Organizational Structure.